A Comparative Analysis of Constitutional Rights in the Gambia and Indonesia - Ousu Mendy (Constitutionale, 2023)
While there is strong advocacy globally on human rights, little attention is paid to constitutional rights in some countries. Many constitutions contain constitutional rights, which are mainly referred to as the bill of rights in their constitutions. This piece presents a comparative exposition of the constitutional rights in The Gambia and Indonesia as constitutional states. Both countries are sovereign, and the strength and lethargy in enforcing these rights in these countries are of great significance in this research. In this research, empirical and normative research approaches are taken to examine both primary and secondary data. Primary materials like the constitutions of the two countries, legislation and court cases on constitutional rights are used. Secondary materials like articles and books are sufficiently used to support this research. Cognizant that a constitution is both a legal and political instrument, the Constitutional Court of Indonesia is undermined to a certain extent by both the House of Representatives and the Executive, and The Gambia’s sparing moments in disobeying High Court orders as regards constitutional rights, this research finally reaches an informed verdict that constitutional rights are different from human rights and approaches to their enhancement ought to be premised on citizenship. The inclusion of legal provisions in constitutions does not, ex cathedra, make institutions strong. Therefore, both countries need a paradigm shift in their national mechanisms to strengthen the institutions that enforce these rights despite the institutional differences in socio-political and socio-legal structures. To do this, the constitutional defense bodies must be comparatively autonomous from other institutions exercising the legislative, executive, and judicial functions to carry out such activities to increase individuals’ and States’ respect for the constitutions and the law and the constitutional rights guaranteed by these constitutions will make fresh and significant strides.